1971
DOI: 10.1139/v71-236
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonyl Chloride Kinetics. Part II. Solvolysis of a Series of Benzenesulfonyl Chlorides: An Unexpected Heat Capacity Variation

Abstract: First order rate constants for the solvolysis of a series of 4-X-benzenesulfonyl chlorides (where X = MeO, Me, Br, and NOz) were measured by the conductance method in HzO over the approximate temperature range of 0 to 25". Pseudothermodynamic parameters, AG*, AH*, AS*, and ACp* were derived and the high accuracy of the rate constants enabled an estimation of dACp*/dT.A trigonal bipyramidal transition state is favored for the nucleophilic attack which is probably by an SN2 type mechanism. A novel explanation fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1975
1975
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In this connection there is a related factor which deserves comment. In an investigation of the hydrolysis of substituted benzenesulfonyl chlorides (43) it was found that the AC,* for the p-methoxy member was less negative than expected by comparison with other members of the series. This was attributed to a temperature dependent interaction of the water with the methoxy group, an effect which increased with increasing temperature as the equilibrium in cooperative water structure moved toward a greater number of unbonded water molecules (44).…”
Section: Discussionmentioning
confidence: 87%
“…In this connection there is a related factor which deserves comment. In an investigation of the hydrolysis of substituted benzenesulfonyl chlorides (43) it was found that the AC,* for the p-methoxy member was less negative than expected by comparison with other members of the series. This was attributed to a temperature dependent interaction of the water with the methoxy group, an effect which increased with increasing temperature as the equilibrium in cooperative water structure moved toward a greater number of unbonded water molecules (44).…”
Section: Discussionmentioning
confidence: 87%
“…In a subsequent paper [ 29 ], for the solvolyses of benzenesulfonyl chloride and its p -MeO, p -Me, p -Br, and p -NO 2 derivatives specific rates of hydrolysis were measured in the 0 °C to 25 °C range. The thermodynamic parameters, ∆ G # , ∆ H # , and ∆ S # and the above mentioned second-order parameter ∆ C p # were derived.…”
Section: Reviewmentioning
confidence: 99%
“…The ∆ C p # values correlated very well against ∆ S # values, except for an unusually low value for the p -MeO derivative. Arguments to explain this [ 29 ] were presented at length but do not seem to be totally convincing.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation